Enforcement of Administrative Environmental Law Against Environmental Pollution by The Flour Industry In Gumelar Village, Gumelar District - Bagus Setiyawan (Faculty of Law Universitas Muhammadiyah Purwokerto, 2022)
AbstractThe environment plays an essential role as a habitat for the survival of living things on earth. Environmental pollution is the entry or input of living things, substances, energy, and/or other components into the environment by human activities to exceed the environmental quality standards set, such as pollution from tapioca flour industrial waste in Gumelar Village. This research aims to find out how to solve problems related to environmental pollution and the inhibiting factors of efforts to solve environmental pollution. This research uses the normative juridical method, where the law is conceptualized as what is written in the legislation. The data collection method in this research uses a literature study and identification and clarification of legal facts. Based on the data analysis carried out in this study, the results showed no solution to the environmental pollution caused by tapioca flour industrial waste. The inhibiting factors in enforcing administrative law on environmental pollution cases are the first many industrial players who do not have permits. Secondly, the lack of public participation in environmental pollution, such as the absence of reports even though liquid waste has polluted the environment.Keywords: Environmental Pollution, Industrial Waste, Administrative EnforcementAbstrak Lingkungan memegang peranan penting sebagai habitat bagi keberlangsungan makhluk hidup di muka bumi. Pencemaran lingkungan hidup adalah masuk atau di masukan nya makhluk hidup, zat, energi, dan/ komponen lain ke dalam lingkungan hidup oleh kegiatan manusia sehingga melampaui baku mutu lingkungan hidup yang telah ditetapkan seperti pencemaran limbah industri tepung tapioka di Desa Gumelar. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana upaya penyelesaian permasalahan yang berkaitan dengan pencemaran lingkungan dan apa faktor penghambat dari upaya penyelesaian terhadap pencemaran lingkungan. Adapun metode yang digunakan dalam penelitian ini adalah yuridis normatif, dimana hukum dikonsepkan sebagai apa yang tertulis dalam peraturan perundang-undangan. Metode pengumpulan data dalam penelitian ini menggunakan studi kepustakaan serta identifikasi dan klarifikasi fakta hukum. Berdasarkan analisis data yang dilakukan dalam penelitian ini diperoleh hasil, belum adanya upaya penyelesaian terhadap pencemaran lingkungan yang disebabkan oleh limbah industri tepung tapioka,. Adapun faktor penghambat dalam upaya penegakan hukum administrasi kasus pencemaran lingkungan terdapat beberapa faktor pertama banyaknya pelaku industri yang belum memiliki izin, kedua kurangnya partisipasi masyarakat terhadap pencemaran lingkungan seperti tidak adanya laporan padahal limbah cair sudah sangat jelas mencemari lingkungan.Kata kunci: Pencemaran Lingkungan, Limbah Industri, Penegakan Administrasi